A low-cost picowatt calorimeter using a flexible printed circuit board - Hanliang Zhu; Yue Zhang; Lan Wang; Jan Brodský; Imrich Gablech; Jianguo Feng; Qi-Long Yan; Shujie Yang; Luke P. Lee; Pavel Neuzil (Nature Communications)
Abstract Calorimetry is crucial in biology, chemistry, physics, and pharmaceutical research, enabling the detection of heat changes at nanowatt and picowatt levels. However, traditional calorimetry systems are often limited by high costs and complex fabrication processes. Here, we reduce the cost and fabrication complexity of microcalorimeters by utilizing widely available flexible printed circuit manufacturing processes. This device achieves temperature and power resolutions of ≈ 6 μK and ≈ 654 pW in vacuum. Its feasibility is validated across a wide range of measurements, including salt crystallization, protein crystallization, and cellular metabolism. Our concept enhances the accessibility of microcalorimeters for high-resolution thermal analysis, which is challenging for conventional calorimeters.